The chaotic journey: Recovering from hip fracture in a nursing home. (November 2016) - Killington, Maggie; Walker, Ruth; Crotty, Maria
Highlights: Nursing home residents who fracture their hips experience disjointed care. Hospital staff struggle to provide people with dementia function focussed care. Nursing home staff lack confidence in providing post-operative care. An outreach rehabilitation program improves quality of life and mobility levels. Integrated care pathways from hospital to nursing home need to be developed. Abstract: Purpose of the study: To understand the journey experienced by nursing home residents following hip fracture and impressions of an outreach rehabilitation program offered after their return home. Design and methods: A qualitative investigation was undertaken in parallel with a randomised controlled trial investigating the efficacy and cost utility of providing a hospital outreach rehabilitation program for older nursing home residents who have recently returned from hospital following hip fracture. Family members and nursing home staff of 28 (out of the first 30) participants (14 from intervention and 14 from control) agreed to participate in interviews and focus groups to provide information and perceptions of each person's journey. NVivo 10 qualitative data analysis software package was used to identify major themes (via open, then axial and finally selective coding). Results: Both family members and staff described nursing home residents with dementia as receiving poor post-operative care from hospital staff who seemed unfamiliar with dementia and delirium. Discharge from hospital soon after surgery (median 4.5 days) occurred with poor transfer of information. Difficulties with residents' emotions, pain management and commencing mobilisation seemed more prevalent within usual care group, whereas fewer overall problems were encountered by those with access to a geriatrician and additional therapy. Implications: This research suggests that an integrated care pathway including the hospital stay and first weeks back at nursing homes should be developed. Performance indicators should include carer measures on the quality of the transfer, pain management measures in the first month and return to walking.